Dynamic thiol/disulphide homeostasis in acute urticaria - Yavuz Otal; Neslihan Özkök Koz; Fatih Ahmet Kahraman; F Güllü Haydar Ercan; Özcan Erel; Gamze Avcıoğlu (Wolters Kluwer Medknow Publications, 2021)
Background: Urticaria is an unknown, sudden, and itchy skin disease that is recognized with redness, swelling, and is sometimes seen with angioedema. It is classified as acute or chronic, depending on the duration of symptoms. Thiols in plasma are powerful antioxidants that physiologically eliminate free radicals. The mostly and rapidly affected proteins are thiols that contain the sulfhydryl group. In the present study, the thiol/disulfide homeostasis was investigated as a brand new indicator of oxidative stress in patients who had acute urticaria and presented to the emergency department. Objective: In the present study, the thiol/disulfide homeostasis, ischemia-modified albumin (IMA), and and neutrophil lymphocyte ratio (N/L ratio) were investigated in the etiopathogenesis of acute urticaria. Material and Method: A total of 37 patients and 40 healthy volunteers were included in the study. Thiol/disulfide homeostasis (TDH) [total thiol-native thiol/disulfide changes] was measured in both groups (patient group and control group) using a brand novel method developed by Erel and Neselioglu. Half of the difference between total thiol and native thiol concentrations gives the amount of disulfide bond. Results: Total thiol and native thiol levels in blood were found to be low. The levels of total thiol (P = 0.218) and native thiol (P = 0,001) were significantly lower in patients with acute urticaria than in the control group. At the same time, the level of disulfide was significantly higher in the patient group than in the control group (P = <0.001). The level of IMA was higher in the patient group than in the control group (P < 0.001). Conclusion: While total thiol and native thiol are low in acute urticaria, the levels of disulfide and IMA are high.